The discovery of the Americas - Maestro, Betsy (Lothrop, Lee & Shepard Books, 1991)
Discusses both hypothetical and historical voyages of discovery to America by the Phoenicians, Saint Brendan of Ireland, the Vikings, and such later European navigators as Columbus, Cabot, and Magellan.